إساءة معاملة طفل الروضة وعلاقتها بتوافقه الاجتماعي من وجهة نظر المعلمات وأسر الأطفال - Al-Wadaei | الوادعي, Amira Mansour | أميرة منصور (Najran University | جامعة نجران, 2023)
The study aimed to examine the abuse of the kindergarten child and its relationship with his social adjustment from the point of view of teachers and the families of the children, and to achieve the main goal of the study, a questionnaire was designed consisting of (73) items distributed on (4) main axes, and their validity and consistency were verified, and the sample of the study was made of (107) kindergarten teacher, and (217) families from the families of children enrolled in kindergartens in Najran, southern Saudi Arabia, and their members were selected using a simple random sample method, and the application was carried out during 2nd term at year 1440/1441 AH | هَدَفَت الدِّارسَة إلى التعرف على إساءة معاملة طفل الروضة وعلاقتها بتوافقه الاجتماعي من وجهة نظر المعلمات وأسر الأطفال.